Trend Analysis of Lung Cancer Incidence and Mortality in Xiamen (2011-2020) - Cong J; Chi J; Zeng J; Lin Y (Risk Management and Healthcare Policy, 2024)
Jianni Cong,1,* Jiahuang Chi,2,* Junli Zeng,3 Yilan Lin2 1School of Health Management, Binzhou Medical University, Shandong, People’s Republic of China; 2Department of Chronic and Non-Communicable Diseases Control and Prevention, Xiamen Center for Disease Control and Prevention, Xiamen, People’s Republic of China; 3Department of Respiratory Center, The Second Affiliated Hospital of Xiamen Medical College, Xiamen, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yilan Lin, Email linyl254@163.comObjective: To analyze the trends of lung cancer incidence and mortality in Xiamen from 2011 to 2020 and provide some clues for the lung cancer prevention and control.Methods: The data was obtained from the Xiamen City Cancer Register in Fujian Province, China. The data was updated on Sep 30, 2023. The codes of C33-C34 were used to identify the lung cancer. The newly diagnosed lung cancer patients during the period of 2011– 2020 in Xiamen City were included in the evaluation of incidence and mortality and Cox analysis.Results: A total of 11408 lung cancer patients were enrolled. The crude incidence rate was 52.78 per 100000 and the age-standardized incidence rate (ASIWR) was 40.67 per 100000 from 2011 to 2020. Both the crude incidence rate of lung cancer (AAPC =5.92, P value < 0.001) and ASIWR (AAPC = 4.93, P value < 0.001) showed increasing trends. The crude incidence rate in female increased 4.90 times faster as that in male (AAPC: 12.34/2.52). The crude mortality rate and the age-standardized mortality rate (ASMWR) were 37.25 per 100000 and 28.30 per100000. The 5-year age-standardized relative survival rate (ARS) was 18.62% (95% CI: 17.63– 19.67%). The 5-year ARS was higher in women than men (26.35% vs 15.28%) and higher in urban than rural areas (21.44% vs 11.96%). Patients with lower education levels had significantly lower ARS than those with higher education (14.66% vs 31.53%). The 5-year ARS improved notably from 2016– 2020 compared to 2011– 2015 (22.23% vs 13.21%). Farmers had the lowest ARS among occupations [13.34% (95% CI:11.93– 14.92%)]. There were all increasing trends in 1-year, 3-year, 5-year, and 10-year ARS rates between 2011 and 2020 (all P values of AAPC< 0.05).Conclusion: Lung cancer incidence in Xiamen increased, while mortality decreased with improved survival. Developing more perfect need to consider the differences in the social environment and other factors.Keywords: lung cancer, incidence, mortality, trend, survival analyze